Update on donor‐derived infections in liver transplantation. Issue 6 (23rd May 2013) - Echenique, Ignacio A.; Ison, Michael G.
<x xml:space="preserve">Abstract</x> Advances in surgical techniques, immunosuppressive medications, and robust infectious disease prophylaxis have resulted in liver transplantation becoming the treatment of choice for patients with end‐stage liver disease and unresectable hepatocellular carcinoma. Nonetheless, organ transplantation is not without risk. Unexpected donor‐derived disease transmission is a newly recognized risk that complicates approximately 0.2% of all organ transplants. We review the epidemiology of donor‐derived infectious diseases and methods of risk mitigation with a focus on liver transplantation. Liver Transpl 19:575–585, 2013. © 2013 AASLD.